2005
DOI: 10.1037/1072-5245.12.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral intervention for stress management in sports.

Abstract: This article covers stress management for athletes beginning with a brief behavioral conceptualization of athletic performance and analysis of stress. Examples of external and internal stressors are offered, as well as of stress responses from autonomic, somatic, and cognitive domains. Further discussed are specific types of stress management approaches used with athletes, and associated with external vs. internal sources of stress, and with the 3 stress response domains. Although the article focuses on the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…For surgeons, energy management techniques, which include relaxation strategies like centered breathing that aim to counter the autonomic response to increased adrenaline, [47][48] may be effective to ensure that arousal is maintained at an optimal level for performance in situations during surgery that cause stress levels to increase. Surgeons may also be able to derive performance benefits from attention and thought management skills, as these techniques may be able to prevent their thoughts from shifting off-target or quickly bring them back on-target, which can help maintain their full concentration to the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For surgeons, energy management techniques, which include relaxation strategies like centered breathing that aim to counter the autonomic response to increased adrenaline, [47][48] may be effective to ensure that arousal is maintained at an optimal level for performance in situations during surgery that cause stress levels to increase. Surgeons may also be able to derive performance benefits from attention and thought management skills, as these techniques may be able to prevent their thoughts from shifting off-target or quickly bring them back on-target, which can help maintain their full concentration to the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46] Comprehensive reviews on the efficacy of imagery to enhance sport performance have shown significant benefits compared to controls. 48 applied with athletes and surgeons of different experience levels and found that imagery is most useful when it is applied to expert performers as a supplemental training tool to refine and improve skills. 8 The authors argued that many surgeons could benefit by adopting imagery as part of their surgical preparation.…”
Section: Mental Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…Behavior techniques can be learned to reduce the effect of external and internal stressors on achieving peak performance [30]. Drawing on ideas from sports psychology, performance-based strategies, such as Anxiety Management Training [31], focus on embedding relaxation techniques and cognitive skills to deal with unhelpful thoughts within the program of skill acquisition.…”
Section: Discussionmentioning
confidence: 99%